Study on PCBs, PCDD/Fs, organochlorine pesticides, heavy metals and arsenic content in freshwater fish species from the River Turia (Spain) - Bordajandi, Luisa R.; Gómez, Gema; Fernández Martín, Mario Antonio; Abad Holgado, Esteban; Rivera Aranda, Josep; González Carlos, María José (Chemosphere, 2003)
9 pages, 3 figures, 3 tables.-- PMID: 12892679 [PubMed].-- Printed version published Oct 2003. In this study samples of common trout, European eel and barbel have been analysed for the levels of heavy metals such as lead (Pb), cadmium (Cd), zinc (Zn), copper (Cu), and the metalloid arsenic (As). Polychlorinated biphenyls (PCBs), including three non-ortho substituted PCBs, 2,3,7,8-substituted polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and DDT and its two main metabolites were also analysed in some selected samples, in order to evaluate the extent of contamination of the River Turia basin. All samples presented detectable levels of the elements analysed, presenting zinc the highest concentrations. European eel was the species found to highly accumulate these contaminants. Regarding organochlorinated compounds, seven samples exhibited detectable levels of the most toxic PCDD/Fs congener, the 2,3,7,8-TCDD. Non-ortho PCBs were not detected or not quantified in almost all samples and the sum of the individual PCB congeners determined were low compared to other aquatic ecosystems with similar fish species. financial support by CSIC (16/98), Junta de Andalucía and LEADER II La Serranía-Rincón de Ademuz. Peer reviewed